High incidence of DNA ploidy abnormalities and increased Mcm2 expression may predict malignant change in oral proliferative verrucous leukoplakia. Issue 4 (24th January 2013) - Gouvêa, Adriele F; Santos Silva, Alan R; Speight, Paul M; Hunter, Keith; Carlos, Román; Vargas, Pablo A; de, Oslei P; Lopes, Márcio A
<x xml:space="preserve">Abstract</x> Aims To assess the DNA content of cases of oral proliferative verrucous leukoplakia (PVL) and correlate the DNA ploidy findings with the expression of Mcm2, geminin, and Ki67, and with clinicopathological data. Methods and results DNA quantification was performed by image cytometry using the ACIS III Automated Cellular Imaging System. Expression of Ki67, Mcm2 and geminin was determined by immunohistochemistry. There were 21 cases of PVL, the female/male ratio was 6:1, and the average age was 65.5 years. Seventeen patients (81.0%) did not report tobacco and alcohol consumption. Nine patients (42.9%) developed verrucous or squamous cell carcinoma. Levels of Mcm2 expression showed a positive correlation with increasingly severe epithelial changes (P = 0.03). Twenty patients had their DNA examined by ACIS III, and 19 (95%) showed aneuploidy. The frequency and severity of aneuploidy (P < 0.0001), the mean values of the DNA heterogeneity index (P < 0.0001) and the 5n‐exceeding fractions (P = 0.0007) increased according to epithelial alterations. Abnormal DNA content was observed even in the more indolent lesions. Conclusions Mcm2 expression and DNA ploidy analysis could be used to predict areas of malignant transformation. The clinicopathological findings associated with the immunohistochemical and DNA ploidy results support the distinct and aggressive profile of this entity.